Application of Division Counting Machine Media for Deaf Students in Division Operation Material - Romadona, Desi Amalia; Lutfiyah, Lutfiyah; Panglipur, Indah Rahayu (Journal of Education and Learning Mathematics Research (JELMaR), 2024)
Media is an effective tool used by teachers to support learning to convey the content of teaching materials. This study aims to determine the application of “division calculation machine” media for deaf students in division operation material. This research uses a descriptive approach with qualitative research. The data sources used are test questions, observation, interviews, and documentation. This research was conducted at SLB ABC Balung with the research subjects as many as 3 high school deaf students. The results of this study by applying the division calculation machine media used to solve division problems can help deaf students to understand the division operation material. Counting using the media “Division Counting Machine” can make it easier for students to count and make counting faster than counting manually although there is 1 student who says it is faster to use the manual than using the media but the student prefers to use the media because there is no need to count and only move the ice cream sticks. Based on this research, the media can make it easier for students to learn division and the media as a facilitator in the learning process in class.